Pregnancy related skin changes and skin diseases (Bangladesh Medical Journal, 2016)
The skin and related structures undergo changes during pregnancy and peurperium. They can be separated into three categories - hormone related pregnancy specific and preexisting. the physiologic changes are mainly of cosmetic importance. The pregnancy specific skin diseases have associated symptoms. Most skin conditions resolve post partum and only require symptomatic treatment. Some of them are associated with an increase in both fetal and/or maternal morbidity and mortality.Bangladesh Med J. 2015 May; 44 (2): 112-116